2021
DOI: 10.5713/ajas.20.0401
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity evolution in the Mexican Charolais cattle population

Abstract: The aim was to characterize the genetic diversity evolution of the registered Mexican Charolais cattle population by pedigree analysis. Methods: Data consisted of 331,390 pedigree records of animals born from 1934 to 2018. Average complete generation equivalent, generation interval, effective population size (N e), and effective numbers of founders (f e), ancestors (f a) and founder genomes (N g) were calculated for seven five-year periods. The inbreeding coefficient was calculated per year of birth, from 1984… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
1
1
Order By: Relevance
“…Núñez-Domínguez et al [55] reported a value of 183 to 827 founders in the Romosinuano breed. The number of founders in the present study exceeds even those reported in other highly selected breeds, such as the Mexican Charolais with a value ranging between 5000 and 13,000 founders [67]. The effective number of nonfounders (N ef ) in this work was 490,067, about seven times higher than the value reported for the Simmental breed (68,400) [64].…”
Section: Probabilities Of Gene Origin and Ancestral Contributionscontrasting
confidence: 68%
See 1 more Smart Citation
“…Núñez-Domínguez et al [55] reported a value of 183 to 827 founders in the Romosinuano breed. The number of founders in the present study exceeds even those reported in other highly selected breeds, such as the Mexican Charolais with a value ranging between 5000 and 13,000 founders [67]. The effective number of nonfounders (N ef ) in this work was 490,067, about seven times higher than the value reported for the Simmental breed (68,400) [64].…”
Section: Probabilities Of Gene Origin and Ancestral Contributionscontrasting
confidence: 68%
“…The number of founders was higher than fe, which was indicative of a reduction in genetic diversity, which may be ascribed to an imbalanced use in the number of founders. The effective number of ancestors (fa) was 162 and higher than the values reported for the Romosinuano breed [55], which ranged between 24 and 31, while in the aforementioned six breeds in Mexico, these values ranged between 33 and 254 [61], which were similar to those in the Charolais, which ranged between 207 and 247 [67].…”
Section: Probabilities Of Gene Origin and Ancestral Contributionsmentioning
confidence: 86%
“…While these values fall below the threshold of 0.6 for reliability in estimates, they have steadily improved since 2000, when the breed was included in the official catalog of Spanish bovine breeds, alongside enhanced management of genealogical records and genetic improvement plans by the association [2]. These values align with other bovine breeds undergoing conservation processes, such as the Curraleiro Pé Duro in Brazil, Italian Pontremolese, Sardo Modicana, and German Angler and Red and White dual-purpose breeds [36][37][38], but are lower than those in commercial-industrial dairy and beef cattle breeds with extensive record-keeping and genetic evaluation histories [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…La proporción del número efectivo de ancestros en relación con el número efectivo de fundadores sugiere que la pérdida de diversidad genética en el período de 1999 a 2018 se debió, en parte, a la formación de cuellos de botella en el pedigrí. Además, la proporción del número efectivo de genomas fundadores en relación con el número efectivo de ancestros sugiere pérdida de alelos fundadores por deriva génica (39) .…”
Section: Estimación De La Diversidad Genética De Ganado Bos Taurus Y Bos Taurus X Bos Indicus Utilizando Información Genealógicaunclassified